Vesper [videorecording (DVD)] - Buožyte, Kristina, 1982-; Samper, Bruno; Samper, Bruno; Clark, Brian (Filmmaker); Chapman, Raffiella; Marsan, Eddie; McEwen, Rosy; Brake, Richard, 1964-; Gaydos, Melanie; Dehn, Edmund (IFC Films, 2023)
After the collapse of Earth's ecosystem, Vesper, a thirteen-year-old girl struggling to survive with her paralyzed father, meets a woman with a secret who will force her to use her wits, strengths, and biohacking abilities to fight for the possibility of having a future.